Socio-distribution Network Analysis: an Exploratory Study of Indonesian Magazine Distribution Channel - Sunardi, Oki; Tjakraatmadja, Jann Hidajat (SBM ITB, 2012)
Indonesian magazine business is characterized by high distribution cost, which constitutes of 60%-70% of the overall enterprise cost. This study aims to investigate the key agents who play significant roles to the distribution coverage in Indonesian magazine market, using social network analysis perspective. Data of 90 agents were collected from five respected publishers of four different major cities. Using ‘roster recalls method’, within 16 months period, 90 agents were interviewed by six field researchers, concerning their social relationship, family relationship, professional/working relationship with other agents. The study found that there are six key agents whose networks will be able to penetrate the Indonesian magazine market. By using only the identified key agents, publishers estimate that 31%-41% of distribution cost could be saved. Future related researches are also suggested in the final conclusion. Keywords: magazine, distribution channel, social network analysis, key agents